Impact of Business Interoperability on the Performance of Complex Cooperative Supply Chain Networks: A Case Study. (7th February 2018) - Cabral, Izunildo; Grilo, Antonio
Abstract : This paper proposes an agent-based model for evaluating the effect of business interoperability on the performance of cooperative supply chain networks. The model is based on insights from the Industrial Marketing and Purchasing network approach and the complex systems theory perspective. To demonstrate its applicability, an explanatory case study regarding a Portuguese reverse logistics cooperative supply chain network is presented. Face-to-face interviews and forms were used to collect data. The findings show that the establishment of appropriate levels of business interoperability has helped to reduce several non-value-added interaction processes and consequently improve the operational performance of the Valorpneu network. Regarding the research implications, this paper extends the current knowledge on business interoperability and an important problem in business: how business interoperability gaps in dyadic organizational relationships affect the network of companies that the two companies belong to—network effect. In terms of practical implications, managers can use the proposed model as a starting point to simulate complex interactions between supply chain network partners and understand better how the performance of their networks emerges from these interactions and from the adoption of different levels of business interoperability.